2019
DOI: 10.1002/ecy.2809
|View full text |Cite
|
Sign up to set email alerts
|

Mucilage‐bound sand reduces seed predation by ants but not by reducing apparency: a field test of 53 plant species

Abstract: An undercited 1983 paper in Ecology by Patricia Fuller and Mark Hay found that seeds of a mint, when the mucilage was wetted and subsequently dried, became encrusted by the sandy desert substrate and that this coating reduced seed predation by harvester ants and rodents. We tested Fuller and Hay's defensive hypothesis in 53 plant species, finding that a mucilage-bound sand coating reduced predation by harvester ants in almost every species tested. While mucilage has many possible functions and probably did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
47
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(48 citation statements)
references
References 39 publications
0
47
1
Order By: Relevance
“…In four cases(Citrus sinensis, Solanum nigrum, Triglochin bulbosa, and Tripleurospermum maritimum), subspecies were used as proxies in the phylogeny. For the genus Narcissus, we used the species N. tazetta for tree pruning(LoPresti et al, 2019). garis, Solanum lycopersicum, and Solanum melongena).…”
mentioning
confidence: 99%
“…In four cases(Citrus sinensis, Solanum nigrum, Triglochin bulbosa, and Tripleurospermum maritimum), subspecies were used as proxies in the phylogeny. For the genus Narcissus, we used the species N. tazetta for tree pruning(LoPresti et al, 2019). garis, Solanum lycopersicum, and Solanum melongena).…”
mentioning
confidence: 99%
“…In contrast, seeds of species of Polemoniaceae were more weakly attached than expected given their mucilage mass; their mucilage composition and primary function of mucilage in nature is thus far unknown but deserves more investigation. We have found that it provides a defensive benefit to several species in the family (LoPresti et al, 2019, Pan et al, 2021, though it was not as protective as mucilage of other families in those studies as well.…”
Section: What Drives Dislodgement Force?mentioning
confidence: 59%
“…The copyright holder for this preprint this version posted September 25, 2021. ; https://doi.org/10.1101/2021.09.25.461784 doi: bioRxiv preprint provides a defensive benefit to several species in the family (LoPresti et al, 2019, Pan et al, 2021, though it was not as protective as mucilage of other families in those studies as well.…”
Section: What Drives Dislodgement Force?mentioning
confidence: 91%
See 1 more Smart Citation
“…Conversely, removal of seeds from animal scat by arthropod granivores, particularly ants, is well‐documented (Levey and Byrne 1993, Passos and Oliveira 2003, Pizo et al 2005, Manzano et al 2010, Fricke et al 2016), and mammalian scat may increase seed predation when its odor attracts arthropods that utilize additional resources found in scat (Sainz‐Borgo 2015). Alternatively, mammalian scat deposition may impede arthropod granivory by reducing seed apparency (Pizo et al 2005) or by acting as a physical barrier to arthropod handling, much like seed mucilage (LoPresti et al 2019). To our knowledge, no research has compared the roles of different granivore guilds (e.g., rodents vs. arthropods) in post‐dispersal predation of seeds deposited in mesopredator scat.…”
Section: Introductionmentioning
confidence: 99%